Layout design and packaging requirements (Journal of the College of Basic Education, 2022)
The current research entitled (Layout Design and Packaging Requirements) focuses on the importance of packaging in advertising goods and how to deliver the advertising message through them. Therefore, the researcher studied the basic concepts of packaging and the difference between the packaging and the cover, and then dealt with the study of packaging as a communicative language through which the typographic designer intends to state and achieve the advertising message through the packaging or the cover or both together.The researcher also determined that the packaging and the packaging are an advertising mediator between the establishment producing the commodity and the commodity itself, which represents the packaging